Psychosocial Determinants Analysis of Husbands' Decisions in the Referral Process for High-Risk Pregnancies in Lumajang Regency - Wahyu Ningtyias, Farida; Setiawati, Hani; Rahmawati, Iis (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2025)
The Maternal Mortality Rate (MMR) due to delayed decision-making remain a major issue, primarily because women and their husbands often do not take an active role as decision-makers. This study aimed to examine the characteristics and influence of various factors including level of knowledge, choice of referral health facility, considerations in hospital selection, family influence, main factors in referral decisions, belief or trust factors, and husband's psychological factors on referral decisions for high-risk pregnancies in Lumajang Regency. The respondents were husbands of pregnant women with a high-risk pregnancy (KSPR ≥ 6) during the period January-June 2023. This quantitative research employed a case-control design using probability sampling.  Cluster sampling was conducted across 25 Community Health Canters, followed by proportionate stratified random sampling, yielding a total sample of 300 participants. The Chi-Square test showed a significant relationship (p<0.05) between psychological factors (p=0.035) and referral decisions for high-risk pregnancies. Meanwhile, other variables including level of knowledge (p=0.893), choice of hospital type (p=0.155), consideration in selecting referral health facilities (p=0.969), family influence (p=0.394), main consideration for referral approval (p=0.901), and belief or trust factors (p=0.702) did not show a significant relationship with husband's referral decision. Binary logistic regression analysis revealed that husband without psychological issues were 2.397 times more likely to agree to referral for high-risk pregnancies compared to those with psychological problems.   Keywords: Husband's decision, referral, delivery, high risk pregnancy